Engineering entrepreneurship from idea to business plan a guide for innovative engineers and scientists - Swamidass, Paul M. (Cambridge University Press, 2016)
"This book is for engineers and scientists who have the aptitude and education to create new products that could become income-producing businesses for themselves and for investors. The book uses short chapters and gets directly to the point without lengthy and distracting essays. The rapid growth in technology-based business plan contests is a clear sign that there are many wealthy inventors looking to make substantial investments in start-ups based on new inventions by inventors, who lack the funds and knowledge to start a business. The key features of this reference enable readers to sharpen their new idea, turn an idea into a commercial product, conduct patent search and complete a provisional patent application, and collect requisite data and prepare a business plan based on a carefully selected business model. Supporting materials are provided on the book's extensive website (www.engineer-entrepreneur-book.com/)." -- Publisher's description.